2019
DOI: 10.24875/ciru.18000664
|View full text |Cite
|
Sign up to set email alerts
|

Self-estimation of surgical skills and competencies based on the learning curve theory in medical residents and fellows

Abstract: Objective: The aim was to explore how in-training junior physicians perceive their surgical performance compared with the one externally rated by their senior surgeon trainers, using a general learning curve model. Methods: Between April and June 2018, a prospective study was conducted at a community hospital associated with a school of medicine. To assess how in-training physicians estimated their surgical performance, 48 surgical residents and fellows were invited to choose one among six options using a scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…31 Once they are confident in performing cases with well-dilated pupils and a moderate grade of cataract, then they can start operating on complicated cases. 32 In our study, we observed that residents often struggled in creating a perfect tunnel; nevertheless, with experience they were more comfortable. A well-formed tunnel reduces surgical time and the risk of intraoperative complications.…”
Section: Resultsmentioning
confidence: 61%
“…31 Once they are confident in performing cases with well-dilated pupils and a moderate grade of cataract, then they can start operating on complicated cases. 32 In our study, we observed that residents often struggled in creating a perfect tunnel; nevertheless, with experience they were more comfortable. A well-formed tunnel reduces surgical time and the risk of intraoperative complications.…”
Section: Resultsmentioning
confidence: 61%
“…As this was a prospective study conceived after the COVID‐19 outbreak, prospective collection of such pre‐pandemic data was unfeasible and as the participation of this study is voluntary, artificial retrospective data on all trainees was unlikely to be a reliable source for comparison due to the likelihood of recall biases. Additionally, there are complexities associated with the value of self‐report measures of efficacy and what it means for clinical practice and competence 19–21 . As self‐report efficacy and self‐reported number of procedures are subjective, these need to be considered with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are complexities associated with the value of self‐report measures of efficacy and what it means for clinical practice and competence. 19 , 20 , 21 As self‐report efficacy and self‐reported number of procedures are subjective, these need to be considered with caution.…”
Section: Discussionmentioning
confidence: 99%
“…No other factor, such as professional experience or experience in minimally invasive surgery showed such a strong correlation. The curve generated for this purpose approximated a classical learning curve [ 26 ]. As described in the introduction, uniform definitions do not exist for experts and novices in surgical disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…However, we lack a common definition for the terms “expert” and “beginner.” As a result, different methods of classification have been used. Distinctions have been made on the basis of professional experience in years, number of operations, or even self-assessment [ 22 , 23 , 24 , 25 , 26 , 27 ]. Specific conditions and the numbers of subgroups in the individual studies vary widely.…”
Section: Introductionmentioning
confidence: 99%